2019
DOI: 10.13057/nusbiosci/n110202
|View full text |Cite
|
Sign up to set email alerts
|

Shoot multiplication of Pogostemon cablin var. Sidikalang and patchouli oil profile

Abstract: Abstract. Hardjo PH, Susanto DPS, Savitri WD, Purwanto MGM. 2019. Shoot multiplication of Pogostemon cablin var. Sidikalang and patchouli oil profile. Nusantara Bioscience 11: 123-127. Pogostemon cablin Benth. is a plant producing patchouli oil, which mostly consists of patchouli alcohol compound. Patchouli oil has great potentials in the world market because of its stability and high price. In this study, in vitro multiplication of Sidikalang variety of Acehnese patchouli shoots was done on solid and liquid M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Both increase blood flow and cause penile swelling to allow for an erection-NO-mediated vasosolidation of the vascular endothelium of the sinusoids and nonadrenergic, noncholinergic and cavernous nerves [25]. Natural aphrodisiac compounds (such as alkaloid, flavonoids, and sponins) stimulate the n-NOS and e-NOS enzymes in the corpus cavernosum (CC).…”
Section: Nitrous Oxide (No) Mechanismsmentioning
confidence: 99%
“…Both increase blood flow and cause penile swelling to allow for an erection-NO-mediated vasosolidation of the vascular endothelium of the sinusoids and nonadrenergic, noncholinergic and cavernous nerves [25]. Natural aphrodisiac compounds (such as alkaloid, flavonoids, and sponins) stimulate the n-NOS and e-NOS enzymes in the corpus cavernosum (CC).…”
Section: Nitrous Oxide (No) Mechanismsmentioning
confidence: 99%
“…var. Sidikalang at concentration 0.2 mg L -1 with addition of 0.2 mg L -1 Kinetin on Murashige and Skoog (MS) medium [9]. Applying cytokinin to the node which contained meristem tissue caused the meristem to grow to form bud.…”
Section: Effect Of Bap To Stimulate Keiki Break or Flower Spikementioning
confidence: 99%
“…Fuller's sunset [6]. Moreover, Hardjo [7] reported that BAP also can use to induce calli formed somatic embryos during 30 d for in vitro propagation of Vanda tricolor Lindl. var.…”
Section: Introductionmentioning
confidence: 99%
“…Among various variety of Pogostemon cablin Benth, the Sidikalang variant is considered as the most outstanding variant in Indonesia, which had international trade quality for production. It is commonly used for patchouli oil supply for various potential function in industry or the medicinal field [4]. However, another various volatile compounds of P. cablin Benth is also needed to be explored of its function.…”
Section: Introductionmentioning
confidence: 99%